Prevalence of Hepatitis G Virus in Liver Disease. (1st December 1999) - Takagi, Hitoshi; Kakizaki, Satoru; Satoh, Ken; Toyoda, Mitsuo; Horiguchi, Norio; Takayama, Hisashi; Kanda, Daisuke; Nakajima, Hiroaki; Ichikawa, Takeshi; Kojima, Akira; Matsuzaki, Yutaka; Shimoda, Ryuya; et al.
Abstract : The prevalence of hepatitis G virus (HGV) in liver disease of non-A, -B, -C viral hepatitis, hepatitis B and hepatitis C was determined. Two of 44 patients (4.5%) with liver injury without any hepatitis A, B or C marker were positive for HGV. One of five cases of hepatocellular carcinoma was positive for HGV. One of three cases with fulminant hepatitis was positive for HGV. This case was negative at the onset of fulminant hepatitis and became positive after plasmapheresis. No patient with acute (n=8) or chronic (n=5) hepatitis or liver cirrhosis (n=8) was positive for HGV in non-A, -B, -C liver disease. One of 30 patients with various HBV-positive liver diseases and nine (17.3) of 52 patients with type C liver disease were positive for HGV. In patients with hepatitis C, four (28.6%) of 14 HGV-co-infected patients were complicated with diabetes mellitus compared with four (10.5%) of 38 single hepatitis C virus (HCV)-infected patients (not significant). In 12 HGV-positive patients, eight of 10 (80%) had a history of blood transfusion. In HCV-positive patients, co-infection with HGV was not a risk factor in patients with diabetes mellitus as a complication. HGV appeared to cause non-A, -B, -C hepatitis rarely, and its main route of infection was blood transfusion.